A Study of the Epiphytic Orchids in Jobolarangan Forest - MARSUSI MARSUSI; CAHYANTO MUKTI; YUDI SETIAWAN; SITI KHOLIDAH; ADIANI VIVIATI (Society for Indonesian Biodiversity, 2001)
The objective of the research was to know the species of epiphytic orchids in Jobolarangan forest. The orchid samples were taken from all stand-plants. The plants were chosen randomly by considering the diversity and richness of orchids that attach on it. Each plant was sampled in three repetitions. Sampling of orchids existence in the plantâ€™s stand were done using transect method through a zonation system. In this research 11 epiphyticorchids such as Bulbophyllum bakhuizenii Stenn, Coelogyne miniata Lindl, Coelogyne rochussenii de Vr.,Dendrobium bigibbum Lindl., Dendrobchilum longifolium, Eria bogoriensis, J.J.S. Liparis caespitosa (Thou.) Lindl., Liparis pallida (Bl.). Pholidota globosa (Bl.) Lindl., Polystachya flavescens (Bl.) J.J.S., and Trichoglottis sp. were found. The host plant stand that was attached with most orchids was Schefflera fastigiata and Saurauia bracteosa, generally in zone three.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKey words: epiphytic orchids, host plants, diversity.